Vehicle speed control using road bumps: Part 2 - Oke, Sunday A.; Salau, Tajudeen A. O.; Adeyefa, Adebayo O. (Transport, 2005)
In a previous publication in this journal the framework for the development of a model for the road bump problem was laid. The current paper focuses on the aspect of determining the effective distance between two consecutive road bumps developing equations governing the velocity and the wavelength of the motion of the vehicle. The wave equation is re‐modelled connecting the isolation factor, linear velocity, wavelength and the frequency of motion of the vehicle over a road bump. A new set of equations is developed to extend the framework earlier presented in Salau et al. The feasibility of the model is demonstrated by its behaviour in graph and simulated data generation. First Published Online: 27 Oct 2010